The Effect of Clinical and Demographic Factors on Quality of Life in End-Stage Renal Disease. A Multicenter Cross-Sectional Study (Journal of Renal and Hepatic Disorders, 2020)
The aim of this study was to assess the quality of life (QoL) in end-stage renal disease (ESRD) patients undergoing hemodialysis and to examine the clinical and demographic attributes associated with it. This is a multicenter, cross-sectional study, conducted in 2018, in which 367 patients with ESRD undergoing hemodialysis were recruited. Data were collected through a two-part anonymous, self-completed questionnaire. The first part contained questions regarding demographic, social, and clinical information, and the Greek version of Missoula–Vitas Quality of Life Index-15 (MVQoL-15) scale was used to assess QoL. Descriptive and inferential statistical methods were applied. All reported p-values were two-tailed, and the statistical significance level was set at 0.05. Of the study participants, 62.1% were male, with a mean age of 61.80 ±15.11. Of the participants, 67.3% were living in urban areas and 59.1% were married. The majority of the Hemodialysis (HD) patients evaluated possessively all the domains of MVQoL except the wellbeing Domain. QoL was found to be influenced, among others, by age (0.001), occupation (0.002), education (0.003), and additional health problems (
Keywords: clinical factors; demographic factors; end-stage renal disease; hemodialysis; quality of life